Implementasi Inovasi Digital M-SKP sebagai Instrumen Transparansi Penilaian Kinerja ASN di Lingkungan Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Madiun - Reydiva Novia Hermawan; Diana Hertati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe and explore the implementation of the digitalization of the Civil Service performance appraisal system through the Madiun Sistem Kinerja Pegawai (M-SKP) platform at the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Madiun City. The conventional manual performance appraisal system creates problems such as subjective bias, limited transparency, and a weak employee performance documentation system. This study uses a qualitative research type with a descriptive approach to analyze the phenomenon of digital transformation in the context of employee performance appraisal. The research findings indicate that the adoption of M-SKP technology contributes substantively to increasing transparency and objectivity in ASN performance evaluation. This digital innovation strengthens the professionalism and accountability of the bureaucracy both at the BKPSDM level of Madiun City and within the Madiun City Government comprehensively. However, the implementation of the system faces several obstacles including the suboptimal digital competence of ASN employees, limited technical infrastructure related to server performance and system maintenance periods, and the dynamics of feature adaptation to follow central government regulations. The implications of the findings indicate that the success of the M-SKP digital transformation requires continuous investment in improving the digital capabilities of civil servants and developing information technology infrastructure through intensive training and mentoring to improve civil servant digital literacy and provide adequate technological infrastructure to maximize the transparency, objectivity, and effectiveness of the performance appraisal system.